Harcownik – nowy typ wizerunku politycznego - Pawełczyk, Piotr (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2012)
The paper discusses the theoretical prerequisites for applying the notion of a political image to the analysis of political reality in terms of marketing. The author particularly emphasizes the personal traits that condition a politician’s image. He indicates that modern mass media demonstrate the need to present politics as both struggle and entertainment. This necessitates the need for politicians’ new images to combine the apparently contradictory features of hero and jester. One of these images is that of a political skirmisher.
The skirmisher – a new type of a political image
Keywords: harcownik; wizerunek polityczny